Parental immigration status and offspring mental health service use for anxiety and depression: A Finnish nationwide register study - Khanal, Prakash; Upadhyaya, Subina; Ståhlberg, Tiia; Heinonen, Emmi; Luntamo, Terhi; Sourander, Andre (Elsevier, 2026)
Background
Despite the megatrend of immigration and subsequent studies on immigrant health outcomes, little is known about how parental immigration status specifically affects offspring mental health service utilization. This register study investigates how parental immigration status relates to offspring mental health service utilization for anxiety, depression, and comorbid anxiety and depression.
Methods
Using Finnish national registers (1992–2006 birth cohort), we analyzed parental immigration status and their association with mental health service use for 33,137 cases matched with 138,957 controls based on age and biological sex. We used multinomial logistic regression to calculate adjusted odds ratios (aORs), controlling for parental age, parity, parental psychopathology, socioeconomic status, and marital status.
Results
Children with two immigrant parents had reduced likelihood of service use for all outcomes: comorbid anxiety and depression (aOR 0.4, 95% CI 0.3–0.6, p < 0.001), depression only (aOR 0.5, 95% CI 0.4–0.6, p < 0.001), and anxiety only (aOR 0.8, 95% CI 0.7–0.9, p = 0.001). Those with immigrant fathers and Finnish mothers showed increased likelihood across all outcomes: comorbid anxiety and depression (aOR 1.6, 95% CI 1.4–1.8, p < 0.001), anxiety only (aOR 1.4, 95% CI 1.3–1.6, p < 0.001), and depression only (aOR 1.4, 95% CI 1.2–1.6, p < 0.001). Maternal immigration <1 year before childbirth lowered service use of comorbid conditions. Children with both parents from low HDI countries and with mothers from Sub-Saharan Africa exhibited significantly lower service utilization.
Conclusion
The significant differences in mental health service utilization among children of immigrant parents suggest that cultural factors, healthcare navigation skills, and migration-related stressors may influence service-seeking behaviors.